Pathogenetic Mechanisms of Diarrhea in Children and Methods for Its Treatment - B.I. Krivuschev (Zaslavsky O.Yu., 2014)
The paper presents the current views on the pathogenesis of acute intestinal infections in children and principles of therapy of diarrhea syndrome. Particular attention is paid to antisecretory therapy and the role of racecadotril in relieving diarrhea.